Expression of KNUCKLES in the Stem Cell Domain Is Required for Its Function in the Control of Floral Meristem Activity in Arabidopsis - Kwaśniewska, Kamila; Breathnach, Caoilfhionn; Fitzsimons, Christina; Goslin, Kevin; Thomson, Bennett; Beegan, Joseph; Finocchio, Andrea; Prunet, Nathanaël; Ó’Maoiléidigh, Diarmuid S.; Wellmer, Frank (Frontiers in Plant Science, 2021)
In the model plant Arabidopsis thaliana, the zinc-finger transcription factor KNUCKLES (KNU) plays an important role in the termination of floral meristem activity, a process that is crucial for preventing the overgrowth of flowers. The KNU gene is activated in floral meristems by the floral organ identity factor AGAMOUS (AG), and it has been shown that both AG and KNU act in floral meristem control by directly repressing the stem cell regulator WUSCHEL (WUS), which leads to a loss of stem cell activity. When we re-examined the expression pattern of KNU in floral meristems, we found that KNU is expressed throughout the center of floral meristems, which includes, but is considerably broader that the WUS expression domain. We therefore hypothesized that KNU may have additional functions in the control of floral meristem activity. To test this, we employed a gene perturbation approach and knocked down KNU activity at different times and in different domains of the floral meristem. In these experiments we found that early expression in the stem cell domain, which is characterized by the expression of the key meristem regulatory gene CLAVATA3 (CLV3), is crucial for the establishment of KNU expression. The results of additional genetic and molecular analyses suggest that KNU represses floral meristem activity to a large extent by acting on CLV3. Thus, KNU might need to suppress the expression of several meristem regulators to terminate floral meristem activity efficiently.